2021
DOI: 10.1103/physrevlett.126.240502
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Quantum Spatial Search with One-Dimensional Long-Range Interactions

Abstract: Continuous-time quantum walks can be used to solve the spatial search problem, which is an essential component for many quantum algorithms that run quadratically faster than their classical counterpart, in Oð ffiffiffi n p Þ time for n entries. However, the capability of models found in nature is largely unexplored-e.g., in one dimension only nearest-neighbor Hamiltonians have been considered so far, for which the quadratic speedup does not exist. Here, we prove that optimal spatial search, namely with Oð ffif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Classically, this problem requires O(N) queries (or, equivalently, time), where N is the number of nodes in the graph-the number of spins in the spin chain. Optimal spatial search is solving this problem with a quantum algorithm [13] in O( √ N) time, and, using the walk Hamiltonian of equation (20), this is possible for α < 1.5 [24]. The quantum algorithm starts by initialising the quantum state of the system as an equal superposition of single-excitation states |s⟩ =…”
Section: Transfer Protocolmentioning
confidence: 99%
See 3 more Smart Citations
“…Classically, this problem requires O(N) queries (or, equivalently, time), where N is the number of nodes in the graph-the number of spins in the spin chain. Optimal spatial search is solving this problem with a quantum algorithm [13] in O( √ N) time, and, using the walk Hamiltonian of equation (20), this is possible for α < 1.5 [24]. The quantum algorithm starts by initialising the quantum state of the system as an equal superposition of single-excitation states |s⟩ =…”
Section: Transfer Protocolmentioning
confidence: 99%
“…The protocol works in the regime where optimal spatial search is possible in the long-range interaction setting [24]. Although the fidelity decreases as the interaction strength increases, these protocols will allow quantum state transfer for α < 1.5.…”
Section: Transfer Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Later research has shown that spatial search by CTQW is optimal for other graph topologies such as the star graph [14,15], graphs with broken links [14], fractal graphs [16], Erdős-Rényi graphs [17], and 1D graphs with long-range interactions [18]. However, general conditions for a graph to be efficiently searchable are not known.…”
Section: Introductionmentioning
confidence: 99%